The effect of drinking water sources due to Cyclone Aila at Shyamnagar, Sathkhira district, Bangladesh (Journal of Tropical Resources and Sustainable Science (JTRSS), 2022)
Bangladesh is the most vulnerable country to disaster and its impact. Coastal Bangladesh along with the Bay of Bengal is the most important and suffered group of cyclone impacts. Cyclone Aila hit the southwestern coast of Bangladesh on 25 May 2009. About two million people were affected and washed away a huge number of households, lives, livestock, crops, and all other resources of the affected area. Water resources in the coastal area are always a term of crisis and even the aila mostly damaged all the resources including surface or groundwater sources. This study focuses on the recovery status of the affected area with considering the drinking water sources. About 36 water samples had been collected for the experiment including rainwater harvesting (6), pond sand filters (6), protected pond (6), and hand tube well (6) from specific six unions of Shyamnagar Upazilla under Sathkhira District in between the time of August to October 2016. A questionnaire field survey was conducted in the most affected coastal area in Bangladesh where about 103 households (309 respondents) participated in their willingness and the study considering their frequency of loss. The results showed a huge dimension of the water crisis and its mitigation. Protected pond and tube well water exceeded the DoE standard for almost all chemical parameters except potassium (3.28 mg/L and 3.75 mg/L), sulfate (377.19 mg/L and 225.66 mg/L), chloride (365.05 mg/L and 349.10 mg/L) and arsenic (1.76±0.25 mg/L and 3.78±1.43). Pond sand filter (PSF) and rainwater harvesting (RWH) had shown the lowest amount of all chemical concentrations compared with another two sources. The respondents face the problem of the distance from the household and the yearly availability of drinking water. They demand monitoring and source management system improvement along with community-based resource management. From the aila event, a huge recovery application is implemented here but these are not sufficient. Respondents gave some opinions to solve this crisis. Considering all aspects, they need a low-cost and more efficient drinking water source to survive their situation.
Keywords: cyclone; impacts; water sources; recovery; Bangladesh